Truck configurations for efficient transportation of forest biomass: a short literature review - Connor Howitt; Mohammad Reza Ghaffariyan (Silva Balcanica)
This literature review aimed to identify the most efficient truck configurations used to transport forest biomass and the factors that affect their transportation efficiency. The review analysed studies that investigated various truck/trailer configurations for transporting forest biomass. The studies considered factors that influenced biomass transport efficiency such as material bulk density, moisture content, hauling distance, maximum permitted truck weight limits, and payload capacities. Recent literature on forest biomass, truck configuration, and productivity were analysed to determine the efficiency of different truck configurations and their fuel usage and emissions. The study reviewed truck configurations for transporting forest biomass and identified that their transportation efficiency was influenced by variables including material density, moisture content, hauling distance, weight limits, and payload capacities. Larger trucks were generally more efficient due to their higher volume and weight limits, except in situations where road access was difficult. The reporting of fuel consumption and emissions for each configuration was inconsistent across international studies. The information presented in this literature review attempts to summarise the recent knowledge of the biomass industry to inform best practice for efficient and cost-effective transportation of forest biomass.